Research Progress of Detection Technology of Viable Foodborne Pathogens - Tingyu LIU; Qingli DONG; Jiaming LI; Hongxiang GAN; Linlin XIAO; Xiaojie QIN (Shipin gongye ke-ji)
Foodborne pathogens are an important factor endangering food safety and public health. Timely and accurate detection of viable foodborne pathogens in foods is the key to ensuring food safety. In recent years, there has been significant development in the detection of viable foodborne pathogens, which is more rapid, accurate, and sensitive than traditional cultures. Therefore, the viable status of foodborne pathogens in foods is summarized in this paper, and the latest research progress of the current viable detection methods of foodborne pathogens is summarized from the perspective of their culturable, nucleic acid, cell membrane integrity, metabolites, and phage. By comparing the advantages and disadvantages of each method, the future development prospects are proposed. The viable pathogens based on phages have unique advantages in terms of specificity, detection speed, and sensitivity, aiming to provide a reference for the development of rapid detection technology for viable foodborne pathogens.